(3eHGOF GdJMdjd GdMbjbjs - (3eMehO eMeO(B, (3cJcJs ((3YeGf(B:s (3LgjfI ddfTQ(B,s, 2001)
(3GdCYOGO GdMbjbjI,eJJGdjGJ heJSdSdGJ GdCYOGO GdMbjbjI,GdfgGjI hGdGJUGd hGdGTJbGb ddEbJQGfGJ,eJJGdjGJ heJSdSdGJ GdGbJQGfGJ,GdJcGeds
(3HHdjhZQGajG(B:(3U(B.191 (3cTGa GdeUWdMGJ(B:(3U(B.433-440s
Keywords: (3GdJMdjd GdQjGVjs; (3GdQjGVjGJs